2018
DOI: 10.3762/bjnano.9.193
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of photothermally active poly(vinyl alcohol) films with gold nanostars for antibacterial applications

Abstract: The unique photothermal properties of non-spherical gold nanoparticles under near-infrared (NIR) irradiation find broad application in nanotechnology and nanomedicine. The combination of their plasmonic features with widely used biocompatible poly(vinyl alcohol) (PVA) films can lead to novel hybrid polymeric materials with tunable photothermal properties and a wide range of applications. In this study, thin PVA films containing highly photothermally efficient gold nanostars (GNSs) were fabricated and their pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
(45 reference statements)
2
34
0
Order By: Relevance
“…The laser-induced heating of gold nanoparticles embedded in an injectable silk protein hydrogel was one of the first examples that used this approach [65]. The NIR laser irradiation at 528 nm for 15 min (450 mW) Poly(vinyl alcohol) (PVA) films cross-linked with citric acid loaded with highly efficient photothermal gold nanostars were also fabricated [66]. The resulting films demonstrated a pronounced photothermal effect under NIR irradiation in the 730-1064 nm wavelength range.…”
Section: Polymeric Nanocomposites Containing Photothermally Active Gomentioning
confidence: 99%
See 1 more Smart Citation
“…The laser-induced heating of gold nanoparticles embedded in an injectable silk protein hydrogel was one of the first examples that used this approach [65]. The NIR laser irradiation at 528 nm for 15 min (450 mW) Poly(vinyl alcohol) (PVA) films cross-linked with citric acid loaded with highly efficient photothermal gold nanostars were also fabricated [66]. The resulting films demonstrated a pronounced photothermal effect under NIR irradiation in the 730-1064 nm wavelength range.…”
Section: Polymeric Nanocomposites Containing Photothermally Active Gomentioning
confidence: 99%
“…Poly(vinyl alcohol) (PVA) films cross-linked with citric acid loaded with highly efficient photothermal gold nanostars were also fabricated [ 66 ]. The resulting films demonstrated a pronounced photothermal effect under NIR irradiation in the 730–1064 nm wavelength range.…”
Section: Reviewmentioning
confidence: 99%
“…Photothermally active monolayers of gold nanostars on glass displayed antibacterial and antibiofilm activity upon NIR laser irradiation , . To introduce the remotely activated by NIR light nanocomposite materials with antibacterial properties, PVA films cross‐linked with citric acid containing highly photothermally efficient gold nanostars were fabricated and their antibacterial properties were studied . It was shown that GNS coated with SH‐PEG‐COOH can act as additional cross‐linking centers.…”
Section: Photothermally Active Polymeric Nanocomposite Materialsmentioning
confidence: 99%
“…T‐test against non‐irradiated samples was performed (* p < 0.05). Adapted from reference under the terms of the creative commons attribution license.…”
Section: Photothermally Active Polymeric Nanocomposite Materialsmentioning
confidence: 99%
“…Beneficial properties of gold, such as good biocompatibility, and excellent resistance to oxidation and acids, promote the applicability of gold nanoparticles in nanomedicine or antibacterial applications [49,50]. On the PVA films containing five-branched gold nanostars (synthesized via a seed-growth method), the eradication of bacteria growth was determined after a laser-induced increase in surface temperature [51]. Using combination of poly(ethylene glycol) (PEG) and Au nanoparticles in hydrogels increased the wound healing efficiency due to the re-epithelization effect and collagen formation [52].…”
Section: Introductionmentioning
confidence: 99%